2015
DOI: 10.1002/ps.4057
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of Spodoptera frugiperda (Lepidoptera: Noctuidae) resistance to the chitin synthesis inhibitor lufenuron

Abstract: Based on genetic crosses, the inheritance pattern of lufenuron resistance in S. frugiperda was autosomal, incompletely recessive and polygenic. Implications of this finding to IRM are discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
79
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 37 publications
(37 reference statements)
2
79
0
5
Order By: Relevance
“…the resistance loci are in autosomal chromosomes. As in most cases of insecticide resistance, other studies have reported autosomal resistance of S. frugiperda , to lambda‐cyhalothrin, carbaryl, lufenuron and spinosad . For the diamide insecticides, the resistance of P. xylostella and T. absoluta was characterized as autosomal and incompletely recessive dominance …”
Section: Discussionmentioning
confidence: 99%
“…the resistance loci are in autosomal chromosomes. As in most cases of insecticide resistance, other studies have reported autosomal resistance of S. frugiperda , to lambda‐cyhalothrin, carbaryl, lufenuron and spinosad . For the diamide insecticides, the resistance of P. xylostella and T. absoluta was characterized as autosomal and incompletely recessive dominance …”
Section: Discussionmentioning
confidence: 99%
“…These insecticides have also been effective against FAW when used on non‐Bt maize in the central‐western region in Brazil and in the USA . However, it is worth mentioning that a high frequency of resistance to spinosad, lambda‐cyhalothrin and lufenuron has already been detected in Brazilian populations of FAW . In contrast, a low frequency of resistance to chlorantraniliprole has been reported in the same populations .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intensive maize cultivation in some regions of Brazil also contributes to the rapid evolution of resistance to insecticides in FAW populations. In these crop production systems, FAW has evolved resistance to several insecticides, such as lambda‐cyhalothrin, chlorpyrifos, spinosad and lufenuron …”
Section: Introductionmentioning
confidence: 99%
“…Sua descoberta teve origem a partir de um programa de seleção de produtos naturais, testando extratos de solo fermentados com potencial de utilização na agricultura e/ou na indústria farmacêutica (THOMPSON et al, 2000). Até o presente momento existem dois produtos comerciais à base de espinosinas no (YU, 1991(YU, , 1992(YU, , 2006CARVALHO et al, 2013;NASCIMENTO et al, 2015). Com a evolução da resistência de S. frugiperda aos inseticidas convencionais, tais como piretroides, organofosforados, carbamatos e inibidores da biosíntese de quitina, as espinosinas se tornaram uma opção para o controle desta praga no Brasil.…”
Section: Introductionunclassified
“…Only one synonymous mutation within the two strains (G567A) was found, showing that the 6 is not the only subunit involved in S. frugiperda resistance to spinosad. (YU, 1991(YU, , 1992(YU, , 2006 CARVALHO et al., 2013;NASCIMENTO et al, 2015). (BIELZA et al, 2007a(BIELZA et al, , 2007b, Drosophila melanogaster (Meigen) WATSON et al, 2010), Spodoptera exigua (Hübner) (MOULTON et al, 2000), Tuta absoluta (Meyrick) (CAMPOS et al, 2014), Plutella xylostella (L.) (BAXTER et al, 2010; (CARVALHO et al, 2013; YU, 1992 YU, , 1993 virescens (YOUNG et al, 2001; ROE et al, 2010), Helicoverpa armigera (Hübner) (AHMAD et al, 2003), P. xylostella (ZHAO et al, 2006) e Spodoptera exigua (Hübner) (WANG et al, 2006).…”
mentioning
confidence: 99%